2012
DOI: 10.3354/meps09447
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale genetic structure and relatedness in the eelgrass Zostera marina

Abstract: The genetic composition of groups of individuals can significantly influence the productivity, resilience, and functioning of communities and ecosystems. For example, the relatedness of individuals within a group often dictates whether their interactions are competitive or cooperative. It is therefore necessary to characterize the genetic structure of populations at spatial scales relevant to these interactions and to determine the distribution of genetic diversity at those scales. Using microsatellite data, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 62 publications
(46 reference statements)
4
57
0
Order By: Relevance
“…Relatedness values in our study can be as high as 0.841 and are comparable to those from a study with Z. marina also at a seascape level (Kamel et al . ). The generally very high relatedness values in both seagrass species (often higher than expected from parent–offspring relationships) can be explained by potential inbreeding (parent–offspring) and by the fact that reproduction is predominantly asexual, with possibly common somatic mutations, which may also be transferred to offspring in plants.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Relatedness values in our study can be as high as 0.841 and are comparable to those from a study with Z. marina also at a seascape level (Kamel et al . ). The generally very high relatedness values in both seagrass species (often higher than expected from parent–offspring relationships) can be explained by potential inbreeding (parent–offspring) and by the fact that reproduction is predominantly asexual, with possibly common somatic mutations, which may also be transferred to offspring in plants.…”
Section: Discussionmentioning
confidence: 97%
“…While there is a body of literature associating heterozygosity with fitness, research on implications of neighbourhood and kinship in seagrasses has only recently been initiated (Kamel et al . ; Stachowicz et al . ) and still deserves further research.…”
Section: Discussionmentioning
confidence: 99%
“…For habitat‐forming species like the eastern oyster and eelgrass, genetic relatedness may be particularly important in determining the effects of genetic diversity on ecological processes given close interactions with conspecifics (Kamel et al. , Stachowicz et al. ) and thus merits consideration in aquaculture design.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in larval dispersal and reproductive traits can affect the degree and scale of population genetic structure (Barbosa et al, 2013;Kamel, Hughes, Grosberg, & Stachowicz, 2012). For instance, various studies have shown that the absence (direct development) or the presence of a larval phase (indirect development)…”
Section: Introductionmentioning
confidence: 99%